Applying Spiritual Aspect of Parenting Skills to Adolescents in the Family - Hamjah, Salasiah Hanin; Zur Raffar, Izzah Nur Aida; Ab. Rahman, Zaizul; Mohamad Rasit, Rosmawati (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Adolescents are important assets to the nation and can potentially bring it to a brilliant and glorious level if prepared with mental ability and good physical condition. However, many social phenomena that involve the demise of moral in the behaviour of adolescents are gradually worrying with the increase of adolescent juvenile cases such as premarital pregnancy, free sex, baby abandonment, skipping school, smoking, taking drugs, rape, prostitution, snatching, stealing, bullying, running away and killing. In this regard, the mastery of parenting skills, especially in the aspect of adolescent spirituality, is one of the measures to tackle the issue of adolescence following home-based education. Hence, this study was conducted to examine parenting skills through the spiritual aspect applied to adolescents in the family in Putrajaya, Malaysia. The design of this research is survey study using questionnaire instrument to 384 respondents selected purposively among parents who have teenage children in Putrajaya. The data were analysed by descriptive statistic technic using SPSS version 22. The study shows that majority of the parents apply parenting skills to adolescents in their families through spiritual aspects by guiding them not to associate God (mean=3.71). This shows that the ‘aqidah education is a major concern in the family. The implications of this study can help parents to strengthen parenting skills in Islamic perspective and apply them in the process of educating adolescents in the family. This study also contributes knowledge to responsible parties in Malaysia such as LPPKN, JAKIM and MoH in managing family affairs and adolescents in Malaysia more effectively.